Self-Control and the Theory of Consumption - Gul, Faruk; Pesendorfer, Wolfgang (Econometrica, 2004)
To study the behavior of agents who are susceptible to temptation in infinite horizon consumption problems under uncertainty, we define and characterize dynamic self-control (DSC) preferences. DSC preferences are recursive and separable. In economies with DSC agents, equilibria exist but may be inefficient; in such equilibria, steady state consumption is independent of initial endowments and increases in self-control. Increasing the preference for commitment while keeping self-control constant increases the equity premium.